Socio-Economic Condition in Relation to Oral and Dental Health Status Through the Study of 184 Iraqi Pupils (Mustansiria Dental Journal, 2018)
The aim of this study is to evaluate the relationship between the social andeconomic condition of the studied pupils with the health of oral and dental conditionand the manifestations inside the oral cavity of those tested pupils reflected thisrelation.A sample of 184 pupils was collected form different middle schools with agesranging between 12-18 years. This sample consists of 84 males and 100 females.The pupils were divided into 3 groups: Group A: pupils with missing fathers andlow income level. Group B: pupils with their fathers and mothers work and of highincome level. Group C: pupils with their mothers being house keepers and of middleincome level.Information related to those groups of pupils were collected and statisticallyanalyzed to obtain the relationships between the socio-economic status of the studiedcases of pupils and the following variations: dental caries, teeth extraction, gingivitis,visits to the dentist and asking oral and dental services and psychological and generalhealth status. The obtained results showed that, gingivitis, loss of teeth and dentalcaries will increase when the socio-economic status decreased and the opposite of thatwas correct. Which means those pathological conditions decreased when the socioeconomiclevel increased. Visits to dentists and asking for dental care depending onthe dental education and the economic level of the pupils, again psychological andgeneral health status also depend on the socio-economic levels, so according to thisstudy many good psychological and health status were found in high income pupils.